2012
DOI: 10.1016/j.radonc.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic cardiac toxicity is predicted by dosimetric and patient factors rather than changes in 18F-FDG PET determination of myocardial activity after chemoradiotherapy for esophageal cancer

Abstract: Purpose To determine factors associated with symptomatic cardiac toxicity in patients with esophageal cancer treated with chemoradiotherapy. Material and Methods We retrospectively evaluated 102 patients treated with chemoradiotherapy for locally advanced esophageal cancer. Our primary endpoint was symptomatic cardiac toxicity. Radiation dosimetry, patient demographic factors, and myocardial changes seen on 18F-FDG PET were correlated with subsequent cardiac toxicity. Cardiac toxicity measured by RTOG and CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 50 publications
4
56
1
Order By: Relevance
“…3D functional cardiac imaging was used to evaluate cardiac toxicity in five papers [10][11][12][13][14]. Treatment details and patient numbers are again listed and marked as the last five papers in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3D functional cardiac imaging was used to evaluate cardiac toxicity in five papers [10][11][12][13][14]. Treatment details and patient numbers are again listed and marked as the last five papers in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Konski et al evaluated 74 esophageal cancer patients using FDG-PET [12]. The FDG uptake declined, especially in the lateral myocardial wall, shortly after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the heart is a mobile structure, and its location may vary both in interfraction and intrafraction relative to the planned CT scan [41]; as a result, the regional dose distribution may be influenced and the segmental location of the two SPECT polar maps may not match very well. All studies of this type suffer from this same limitation.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of esophageal cancer using definitive regimen of 60 Gy with concurrent chemoradiotherapy, investigators from Japan reported that the optimal V20 threshold to predict symptomatic radiation pneumonitis (grade 2) was 30.5 % [22]. Konski and colleagues proposed thresholds for symptomatic cardiac toxicities (pericardial effusion, myocardial infarction, and sick sinus syndrome) for whole-heart V20 of 70 %, V30 of 65 %, and V40 of 60 % [23]. Wei and colleagues performed an analysis of pericardial effusion risk from DVH parameters among patients treated with definitive chemoradiotherapy [24].…”
Section: Dose Constraintsmentioning
confidence: 99%